Clinical assessment of urinary prostate cancer antigen 3 in Chinese population: a large-scale, prospective and multicenter study - Xuan Shu; Jiaming Wang; Wen Cai; Shen Lin; Jiangfeng Li; Xueyou Ma; Yufan Ying; Yat Sai Terry Wang; Xiao Wang; Hong Chen; Chunyu Jin; Ben Liu; et al. (World Journal of Surgical Oncology)
Abstract Background To assess the clinical utility of PCA3 in the diagnostic accuracy, the correlation between PCA3 and biopsy or pathological characteristics and the performance of PCA3 to reduce the unnecessary biopsies in Chinese population. Methods A prospective study including patients with indication of prostate biopsies from 4 centers was conducted. All patients underwent PCA3 urine tests and prostate biopsies. The PCA3 score was analyzed by PCA3 gene expression Detection Kit (Fluorescent RT-PCR) (York biotech, Cat.#YDM-B01, China). Base model (clinical information) and PCA3 model (PCA3 scores and clinical information) were constructed via multivariate logistic regression. Discrimination, calibration and decision curve analysis were evaluated. Results In 1117 patients, 587 men with positive biopsy results had higher median PCA3 scores than those with negative biopsy results (p < 0.001). PCA3 scores had a greater area under the curve (AUC) than tPSA, %fPSA and PSAD in all PSA levels or PSA gray zone (4–10 ng/ml). Men with biopsy Gleason score < 7 had lower median PCA3 scores than those with Gleason score ≥ 7 (p = 0.016). In radical prostatectomy specimens, PCA3 scores were significantly associated with high-grade PCa (p = 0.002) and EAU biochemical recurrence risk (p = 0.044), but not extracapsular extension (p = 0.072), seminal vesicle invasion (p = 0.482) and T stage (p = 0.457). Regression analysis showed that the AUC increased from 0.806 (base model) to 0.873 (PCA3 model). PCA3 model with cutoff 0.15 could reduce 35.3% prostate biopsies and delay 5.8% high-grade PCa. Conclusions PCA3 had a better diagnosis accuracy than tPSA, %fPSA and PSAD. PCA3 was a significantly independent predictor for risk stratification, suggesting that PCA3 could provide incremental value to reduce unnecessary prostate biopsies.